Building A Smart Generation In Media: Socialization Of The ITE Law For The Young Generation - Sihutami, Veronica Kinanthi; Fobia, Maranatha Lisatyaningrum Hainekam; Purwati, Purwati (JURNAL HUKUM SEHASEN, 2025)
The development of information technology provides wide access to information and digital interaction. However, the lack of legal literacy among the younger generation often leads to violations that have negative impacts, such as the spread of rights, violations of privacy and cyberbullying. This community service activity aims to improve the understanding of junior high school students about the ITE Law, digital literacy and media ethics. The socialization methods used include interactive presentations, group discussions and legal case simulations. Pre-test and post-test evaluations showed an increase in understanding of digital law by up to 80%. This activity succeeded in equipping students with basic knowledge about digital ethics, data security and the legal implications of online activities.